Estratégias de uma indústria diante do desafio da mudança de regime tributário: um estudo de caso - Castanhetti, Liliane da Silva (2022)
The objective of this work was to present and analyze alternatives and strategies for the financial balance of the Alpha Industry in the face of a change in the tax regime. The company went through the process of disqualification from Simples Nacional, making it necessary to choose between the tax regimes of Real Profit or Presumed Profit. Its methodology is characterized as applied and quantitative in nature with the Monte Carlo Simulation tool, using the @Risk software, in addition to the horizontal and vertical analysis of Total Revenue, costs, expenses and net income for the period. Furthermore, it makes use of a descriptive approach, with regard to its objective; in addition, it uses bibliographic and documental files regarding the data collection procedure. Also with regard to data collection, Alpha Industry made available the Income Statement (DRE) for the 60 months within the Simples Nacional regime. The industry data was updated according to inflation for January 2022 values by the Broad Producer Price Index – IPA-M. The results of the simulation of the tax regimes indicated that the Real Profit is the most suitable for the company studied. The intervention proposal is the adoption of the indicated tax regime and strategies to increase revenue with marketing, market expansion and product diversification. In addition, studies were suggested in the fiscal area, in cost control and improvements in labor, technology and processes. For a more detailed analysis, strategic tools such as SWOT, Canvas and BCG Matrix can be used